Cloud database development and management - Chao, Lee, 1951- (Taylor & Francis, 2014)
"Nowadays, cloud computing is almost everywhere. However, one can hardly find a textbook that utilizes cloud computing for teaching database and application development. This cloud-based database development book that teaches both the theory and hands-on practice with step-by-step instructions and examples. This book helps readers to set up a cloud computing environment for teaching and learning database systems. The book will cover adequate conceptual content for students and IT professionals to gain necessary knowledge and hands-on skills to set up cloud based database systems"--